The notion of language in language education policy: a comparative analysis of Lithuania and Denmark - Urbonaitė, Daina (Taikomoji kalbotyra, 2017)
The article analyses the notion and ideology of language formed at the state level in Lithuania and Denmark. The aim is to examine the notion of language and the understanding of language functionality conveyed in the documents of language education policy and ideology emerging in them, also the purposes raised for language education. The official language education policy formed by the state exerts direct influence on language teaching at school and on the students’ formation of the notion of language. Therefore, the questions raised in this research are aimed at identifying what is implemented with the official language education policy, how much attention is devoted to developing the students’ communicative, argumentative skills and skills of independent critical thinking, and how much the policy focuses on the advocacy of national ideology and identity.The data of the research includes national language education policy documents which determine the implementation of language policy in the system of education of Lithuania and Denmark. The following aspects have been analysed: language functions as presented in the education policy documents: the communicative function and the function of national identity; the formation of ideology of nationality through language education; the formation of standard language ideology in language education policy; also the students’ linguistic competences to be developed at school.The results have shown that the notion of language emerging in the Lithuanian language education policy documents encompasses ideologies of standard language, language correctness and linguistic nationalism. The main goal of the Lithuanian language teaching is the implementation and strengthening of a single standard language norm and the formation of the notion of language as a protector and disseminator of national identity. However, the aim to develop language as a communicative tool as well as to develop the students’ critical thinking is also identifiable. The main goal of the Danish education policy is the development of the students’ communicative language function, critical-analytical thinking, and the formation of the notion of language as a means of communication, as well as of the notion of linguistic variation.
Keywords: standard language ideology; standard language; language correctness; linguistic variation; communicative language function; language function of national identity